Advances in catalysis. - Gates, Bruce C.; Jentoft, Friederike C. (Advances in catalysis, 2013)
Advances in Catalysis fills the gap between the journal papers and the textbooks across the diverse areas of catalysis research. It records progress in the field of catalysis and provides the scientific community with comprehensive and authoritative reviews.